«Imagine in your head» – How Teaching Artists write with primary school students - Beckert, Christiane; Gyger, Mathilde; Supino, Franco (Swiss Journal of Educational Research, 2017)
In the run-up to the football World Cup 2014, four established authors acted as Teaching Artists in primary school classes in Northwestern Switzerland. In the project kick&write® 2014, they led writing workshops which aimed at motivating children with an unfavorable literacy socialization to read and write. Their task was to write a text on football. To appoint Teaching Artists as writing coaches is a special school support measure in the area of literacy. This contribution specifies the artistic and educational (German didactics) aims and concepts of the Teaching Artists and documents their perception of the children’s creative process. In this place of informal education, reading motivation increased, because of an unusual access to literacy, the experience of competency beyond formal norms of language, communication linked to these literary activities, and intensive support.